Disruption of boreal lake circulation in response to mid-Holocene warmth; evidence from the varved sediments of Lake Nautajärvi, southern Finland - Lincoln, Paul; Tjallingii, Rik; Kosonen, Emilia; Ojala, Antti; Abrook; Ashley; M.; Martin-Puertas, Celia (Elsevier, 2025)
Future climate projections are expected to have a substantial impact on boreal lake circulation regimes. Understanding lake sensitivity to warmer climates is therefore critical for mitigating potential ecological and societal impacts. The Holocene Thermal Maximum (HTM; ca 7-5 ka BP) provides a valuable analogue to investigate lake responses to warmer climates devoid of major anthropogenic influences. Here, we analyse the micro-X-ray core scanning profiles (μ-XRF) of the annually laminated (varved) sediments from Lake Nautajärvi (NAU-23) in southern Finland to elucidate changes in lake circulation and sedimentation patterns. Principal component analysis (PCA) identifies two key components in the geochemical data associated with the nature of the sediments, i.e. detrital vs organic sedimentation (PC1), and hypolimnetic oxidation (PC2). Our findings reveal that during the HTM, the lake became more sensitive to changes in oxygenation and mixing intensity. These changes were triggered by a warmer climate, which increased organic matter and redox sensitive metal solute concentrations in the water column, strengthening lake stratification and weakening dimictic circulation patterns. Superimposed on HTM weakened circulation are distinct phases of increased oxidation and iron-rich varve formation that do not happen when the background conditions are cooler (i.e. the early and late Holocene). This is driven by temporary strengthening of the mixing regime in response to climatic variability and storminess cycles across southern Scandinavia. These findings demonstrate that whilst warmer conditions weaken boreal lake circulation regimes, they can also make them increasingly vulnerable to short term oscillations in prevalent climatic conditions and weather patterns, which could have significant impacts on lake water quality and aquatic ecosystems. These findings underscore the non-stationary nature of lake sensitivity to short-term climatic variability and emphasize the potential for similar shifts to occur under future warming scenarios.